Effect of self-assembled peptide-mesenchymal stem cell complex on the progression of osteoarthritis in a rat model - Kim, Ji Eun; Lee, Sang Mok; Kim, Soo Hyun; Tatman, Phil; Gee, Albert O.; Kim, Deok-Ho; Lee, Kyung Eun; Jung, Youngmee; Kim, Sang Jun (DOVE MEDICAL PRESS LTD, 2014)
Purpose: To evaluate the efficacy of mesenchymal stem cells (MSCs) encapsulated in self-assembled peptide (SAP) hydrogels in a rat knee model for the prevention of osteoarthritis (OA) progression. Materials and methods: Nanostructured KLD-12 SAPs were used as the injectable hydrogels. Thirty-three Sprague Dawley rats were used for the OA model. Ten rats were used for the evaluation of biotin-tagged SAP disappearance. Twenty-three rats were divided into four groups: MSC (n=6), SAP (n=6), SAP-MSC (n=6), and no treatment (n=5). MSCs, SAPs, and SAP-MSCs were injected into the knee joints 3 weeks postsurgery. Histologic examination, immunofluorescent staining, measurement of cytokine levels, and micro-computed tomography analysis were conducted 6 weeks after injections. Behavioral studies were done to establish baseline measurements before treatment, and repeated 3 and 6 weeks after treatment to measure the efficacy of SAP-MSCs. Results: Concentration of biotinylated SAP at week 1 was not significantly different from those at week 3 and week 6 (P=0.565). Bone mineral density was significantly lower in SAP-MSC groups than controls (P=0.002). Significant differences in terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick-end labeling staining between the control group and all other groups were observed. Caspase-8, tissue inhibitor of metalloproteinases 1, and matrix metalloproteinase 9 were diffusely stained in controls, whereas localized or minimal staining was observed in other groups. Modified Mankin scores were significantly lower in the SAP and SAP-MSC groups than in controls (P=0.001 and 0.013). Although not statistically significant, synovial inflammation scores were lower in the SAP (1.3 +/- 0.3) and SAP-MSC (1.3 +/- 0.2) groups than in controls (2.6 +/- 0.2). However, neither the cytokine level nor the behavioral score was significantly different between groups. Conclusion: Injection of SAP-MSC hydrogels showed evidence of chondroprotection, as measured by the histologic grading and decreased expression of biochemical markers of inflammation and apoptosis. It also lowered subchondral bone mineral density, which can be increased by OA. This suggests that the SAP-MSC complex may have clinical potential to inhibit OA progression.